CHARACTERISTICS OF THE NOTION OF "MERCHANT" AND "COMMERCIAL CONTRACT" IN THE PROVISIONS OF THE COMPANIES ACT AND THE CONTRACTS AND TORTS ACT OF THE REPUBLIC OF MACEDONIA - Čavdar, Kimo K (Pravni zapisi, 2013)
The definition of the notions of "merchant" and "commercial contract" in the legal system of the Republic of Macedonia, particularly concerning the application of the Contracts and Torts Act becomes an issue because in everyday legal transactions there is a number of relations in which merchants participate, concluding commercial agreemetns, and is hence necessary to identify the cases in which the provisions applicable to such transactions are different to those usually applicable to everyday material transactions concluded by entites that are not engaged in merchant business. The purpose of this paper is to explain how the Companies Act of the Republic of Macedonia regulates the notion of "merchant" and how does that notion reflect on the provisions of the Contracts and Torts Act governing commercial contract. The paper has four subtitles - first - the Introduction, second -a Brief Overview of the Contents and Organisation of the Subject-Matter in the Contracts and Torts Act (CTA) in the Republic of Macedonia, third - the Uniform Regulation of Civil and Commercial Contracts and, In General, More on the Notions of "Commercial Contract" and "Merchant" Regulated by the CTA/RM and CA/RM and fourth - Some Provisions of the CTA/RM Governing Commercial Contracts. The introduction of the paper indicates that the general provisions of the Contracts and Torts Act of the Republic of Macedonia (CTA/RM) refer to the notions of "merchant" and "commercial contract" and that the further provisions of this statute regulate certain situations when these notions are used due to the specific nature of commerical relations. It also indicates that the notion of "merchant" is not specially defined in the CTA/RM, and that consequently that statute relies on the notion of "merchant" regulated by the Companies’ Act (CA). The second part of the paper gives a short overview of the contents and the organisation of the subject-matter in the CTA/EM, coupled with a statement that the manner in which the CTA/RM regulates civil and commercial obligation relations uses as its starting point the so-called "commercialisation of civil law", which is both applied in practice and elaborated in legal science. The third part of the paper decribes the notion of "merchant" as regulated in the Republic of Macedonia, by the provisions of the Companies’ Act. This section of the paper refers to the definition of the notion of "company", which includes a merchant’s venture in terms of the Companies’ Act and states that a company is a set of rights, objects and factual relations that have a material value and belong to the merchant’s commercial activity, where these elements comprise the merchant’s assets, but also include his obligations. It can consequently be concluded that the legal capacity belongs to the merchant, not to the company; the merchant is the bearer of the company (hence the term "entrepreneur"), and when a company participates in trading, it is only an instrument used by the merchant to realise his operation (business venture). Hence, this part of the paper also describes the notion of a company, as regulated by the Companies’ Act. The fourth part indicates that the CTA/RM has three groups of provisions applicable to commercial transactions. With regards to some situation that may arise concerning any contractual relations, the CTA/RM expressly prescribes specific rules regarding commercial contracts. Some contracts may be concluded only by merchants, and there are also cases when one provisions concerning all contractual relations may be applied in the same manner both concerning a commercial contract and a contract that cannot be considered a commercial contract. Finally, it can be concluded that the Contracts and Torts Act of the Republic of Macedonia, which constitutes a codification of the law of obligations, does regulate commercial contracts and that therefore there is no need to adopt a special commercial code which would, in addition to regulating companies, also regulate commercial contracts. This also means that the modern concept of "commercialisation of civil law" is accepted in Macedonia; the relevant statute regulates both the general civil transactions and more specific, commercial transactions and contracts. The author bears in mind the fact that general theories concerning obligations are also applicable to commercial transactions, whereas these institutes are not dealt with separately concerning commercial transactions either in practice or in theory. When it comes to the need to regulate certain issues, given the specific nature of commercial transactions, these needs are satisfied by the introduction of special provisions concerning such transactions in the CTA. Consequently, it can be concluded that the CTA/RM, regulates the issues concerning the unification of general law of obligations and the law governing commercial contracts in a modern manner, following the examples of Switzerland, Italy, Serbia and Croatia. . Key words: merchant, commercial contract, commercialisation of civil law, penalty interest, reference rate, law of obligations, nominated contracts, companies.